Modified Humic Acid from Peat Soils with Magnetite (Ha-Fe3O4) by Using Sonochemical Technology for Gold Recovery (Universitas Negeri Semarang, 2020)
Sonochemical technology is a technology that involves ultrasonic waves in chemical reactions. In this study, humic acid isolated from peat soil has been successfully modified with magnetite (HA-Fe3O4) using sonochemical technology. Characterization of the physical and chemical properties of HA-Fe3O4 was carried out using FTIR, XRD, SEM and VSM. HA-Fe3O4 was used for recovery of gold from simulated gold waste (HAuCl4). FTIR characterization showed that the interaction between HA and Fe3O4 was through hydrogen bonds. The crystal size of HA-Fe3O4 using the Debye-Scherrer equation based on the XRD diffractogram was 12.4 nm. The saturation magnetization value of HA-Fe3O4 obtained was 52.80 emu/g. Adsorption studies at various pH showed that HA-Fe3O4 has been successful in recovering of gold from simulated gold waste. The % recovery of gold was 99%. Gold recovery occurs through the adsorption process followed by reduction of Au (III) to Au(0).